PLURALISM AS DIVINE ORDINANCE: Ahmad Sonhaji’s Contextual Tafsîr and the Construction of Muslim Identity in Singapore - Muchtar, M. Ilham; Amin, Saifuddin (State Islamic University North Sumatra, 2025)
This study examines the contextual Qur’anic interpretation developed by Ahmad Sonhaji and its influence on Muslim identity formation within Singapore’s multicultural and secular social order. As a prominent religious scholar, Sonhaji articulates pluralism as part of divine ordinance, emphasizing justice, coexistence, and ethical engagement with religious diversity. Employing a qualitative research design, this study combines textual analysis of Sonhaji’s tafsir writings with semi-structured interviews involving Islamic educators in Singapore to assess the transmission and reception of his interpretive framework within Islamic educational institutions.““The findings demonstrate that Sonhaji’s contextual tafsir offers a locally grounded yet theologically coherent approach that reconciles Islamic normative teachings with the realities of plural society. His interpretation reinforces Muslim identity not through exclusivism, but through ethical responsibility, civic engagement, and interfaith respect. Integrated into both formal curricula and digital learning platforms, his ideas encourage critical thinking and participatory religious understanding, particularly among younger Muslims. This study argues that Sonhaji’s work represents an important model of localized Qur’anic scholarship that contributes to contemporary tafsir studies and Muslim minority discourse. It highlights the significance of context-sensitive interpretation in enabling Muslim communities to navigate diversity while maintaining religious authenticity.